Relationship between anion gap and 28-day all-cause mortality in patients with acute pulmonary edema: A retrospective analysis of the MIMIC-IV database - Ping Guo; Yuwen Liu; Xiaomi Huang; Yanfang Zeng; Zhonglan Cai; Guang Tu (PLoS ONE, 2025)
Background Acute pulmonary edema is a severe clinical condition with high mortality. The anion gap, reflecting metabolic acid-base disturbances, is often elevated in critically ill patients. However, its relationship with outcomes in acute pulmonary edema remains unclear. Objective To explore the association between admission anion gap levels and 28-day all-cause mortality in patients with acute pulmonary edema. Methods This retrospective cohort study utilized data from the MIMIC-IV database (2008–2019) and included adult patients with acute pulmonary edema. Patients were categorized into quartiles based on anion gap levels. Cox regression models analyzed the relationship between anion gap and mortality, with restricted cubic spline (RCS) curves, Kaplan-Meier analysis, and subgroup analyses. Results A total of 1094 patients were included. Univariate Cox regression showed a positive correlation between anion gap levels and 28-day mortality (HR = 1.13, 95%CI: 1.09–1.17, P < 0.001). Multivariate analysis confirmed anion gap as an independent predictor (HR = 1.11, 95%CI: 1.07–1.15, P < 0.001). The RCS curve indicated a nonlinear relationship, and Kaplan-Meier analysis showed lower survival in higher anion gap groups (P < 0.001). Subgroup analysis revealed significant interactions between age and renal disease status, indicating that anion gap levels had a stronger association with mortality in younger patients and those without renal disease. Conclusion Admission anion gap levels predict 28-day all-cause mortality in acute pulmonary edema patients, particularly in younger patients and those without renal disease. Clinically, anion gap monitoring should be emphasized, and individualized prognostic and treatment strategies should be developed with factors like age and renal status to improve outcomes.